Accounting Treatment of Corporate Social Responsibility at PT Angkasa Pura I (Persero) International Airport I Gusti Ngurah Rai - Bali - Lady Biansa Manora Hidayat; I K Suandi; I M Suarta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
Social responsibility accounting is a tool for companies to disclose social activities as a form of accountability to stakeholders and the community. The aim of this research is to analyze the social responsibility accounting treatment at PT AP I Bali Branch Office. Collecting data in this research using documentation techniques. In the validity of the data using a credibility test which is carried out by triangulation and holding a member check. This research uses a descriptive qualitative analysis technique. The results of the research indicate that (a) PT AP I Bali Branch Office in presenting reports on social responsibility outside of financial statements is in accordance with what is stated in PSAK No. 1 Regarding the Presentation of Financial Statements and (b) the social responsibility accounting reports carried out by PT AP I Bali Branch Office are in accordance with Law no. 40 of 2007 concerning Limited Liability Companies and Ministerial Regulation PER-02/MBU/04/2020 are reviewed through the form of the PKBL Report which is in accordance with the report format in the Circular Letter of the Minister of BUMN No. SE-02/MBU/Wk/2012.